Resource Management for Device-to-Device Underlay Communication - Song, Lingyang; Han, Zhu.; Xu, Chen.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Device-to-Device (D2D) communication will become a key feature supported by next generation cellular networks, a topic of enormous importance to modern communication. Currently, D2D serves as an underlay to the cellular network as a means to increase spectral efficiency. Although D2D communication brings large benefits in terms of system capacity, it also causes interference as well as increased computation complexity to cellular networks as a result of spectrum sharing. Thus, efficient resource management must be performed to guarantee a target performance level of cellular communication. This brief presents the state-of-the-art research on resource management for D2D communication underlaying cellular networks. Those who work with D2D communication will use this book$1 (Bs information to help ensure their work is as efficient as possible. Along with the survey of existing work, this book also includes the fundamental theories, key techniques, and applications.s
Introduction -- Physical-layer Techniques -- Radio Resource Management -- Cross-layer Optimization -- Summary.
Keywords: Computer science; Computer Communication Networks; Telecommunication; Computer Science; Computer Communication Networks; Communications Engineering, Networks